IMPLEMENTASI PBL BERBANTUAN WORDWALL DALAM PEMBELAJARAN GEOGRAFI GUNA MENINGKATKAN MINAT BELAJAR DAN BERPIKIR KRITIS SISWA - Maharani Purba, Putri; Sriartha, I Putu; Ananda Citra, I Putu (Program Studi Pendidikan Geografi Universitas PGRI Sumatera Barat, 2026)
This research aims to: (1) describe and analyze the implementation of the Wordwall-assisted Problem-Based Learning (PBL) model in geography education; (2) test the effectiveness of implementing the Wordwall-assisted PBL model in enhancing students' Learning Interest; and (3) test the effectiveness of the Wordwall-assisted PBL model in improving students' Critical Thinking Skills. This study was conducted at SMA Negeri 3 Singaraja using a Quasi-Experimental design, specifically the Non-Equivalent Control Group Design. The selection of experimental and control groups was carried out in classes with equivalent cognitive levels. Data were collected through observation and testing methods, which were then analyzed using descriptive statistics and inferential analysis (N-Gain Score). The results of the study indicate that: (1) the implementation of the Wordwall-assisted Problem-Based Learning model in geography learning was carried out in the ‘Very Good’ category with an average score of 81.91; (2) the N-Gain analysis showed that the Wordwall-assisted PBL model was ‘Moderately Effective’ (69.05%) in increasing students’ Learning Interest; and (3) the N-Gain analysis revealed that the model was ‘Moderately Effective’ (61.01%) In improving students’ Critical Thinking Skills. Based on these findings, the integration of the Problem-Based Learning model with Wordwall media can serve as an innovative alternative strategy to optimize students’ learning interest and critical thinking abilities in geography education.